Isotopic and elemental characterisation of Italian white truffle: A first exploratory study. (November 2020) - Bontempo, Luana; Camin, Federica; Perini, Matteo; Ziller, Luca; Larcher, Roberto
Abstract: White truffle ( Tuber magnatum Pico ) is a typical product of some Italian regions, and due to its organoleptic properties it is of high economic value. To date, there is no available information on the elemental and isotopic composition of this product. For the first time the characteristic value ranges of the stable isotope ratios of the bio-elements as a whole (δ 13 C, δ 15 N, δ 18 O and δ 34 S) and of the concentration of some macro- and micro-elements (Ag, Al, B, Ba, Ca, Cd, Cr, Cu, Fe, K, Li, Mg, Mn, Na, Ni, Pb, Sr, Zn) are now available, determined in white truffles produced in different areas of Italy (Toscana, Molise, Marche, Piemonte - Langhe, Monferrato-) and in Croatia. All the samples analysed showed values for the toxic, potentially toxic or allergenic elements lower than the legal limits. Furthermore, the ranges of variability of some elements or elements ratios (i.e. Na, B, Mg/Ca, Ba/Ca, Sr/Ca, Li/Fe, B/Al, Ba/Al) and stable isotope ratios (δ 34 S and δ 18 O) seem to be different according to the geographical origin. Therefore, the results of this first exploratory work highlight the possibility of characterising white truffles of different provenance, and suggest widening the scope of the survey throughout Italy and foreign regions. Highlights: For the first time isotopic and elemental data were determined in Italian white truffles. Truffles isotopic and elemental data are related to geography and geology of growth area. Langhe white truffle present lower values of δ 18 O (<19‰) and Na (<75 mg/kg). Monferrato white truffle have peculiar values of δ 34 S (<-3‰) and of δ 18 O (mean value 19.9‰). Croatian white truffles show lower values of B (<0.32 mg/kg), Sr/Ca and Mg/Ca ratios (<0.003 and < 0.6).